The Brazilian Reform of Transfer Pricing Rules: Complying with the OECD’s Standards - Marciano Godoi; Melody Furman (Acta Universitatis Lodziensis Folia Iuridica)
The article analyses the international context that led to a broad reform of Brazilian domestic legislation on transfer pricing. The former Brazilian transfer pricing legislation (1996) lacked compliance with the comparability analysis and the arms’ length principle. The new legislation, published in 2023, adopted the Organisation’s for European Economic Cooperation (OECD) guidelines on the subject. One important issue that may arise from implementing the new rules and the comparability analysis in Brazil is the relative lack of databases on the subject.